Management of Teachers-Parents Relationship to Improve Teacher Subjective Well-Being: A Literature Review - Handayani, Yunita Sri (Psychological Research on Urban Society, 2023)
The relationship between teachers and parents plays an important role not only in determining the success of student learning at school but also in influencing the subjective well-being of teachers. However, the ideal teacher-parent relationship is not always possible. Often there are conflicts between parents and teachers that make student learning outcomes at school not optimal. A poor relationship between teachers and parents will also reduce the subjective well-being of teachers. This paper will analyze the management of good teacher-parent relationship to improve the subjective well-being of teachers. This study uses a literature review method from 14 research journal articles to identify the problems that become barriers on parents teacher relationships. The study found that differences in perceptions of student abilities between teachers and parents caused the most conflicts in the teacher-parent relationship. Furthermore, the results of the study found that trust and communication skills are two important elements for managing teacher-parent partnerships which ultimately play a role in increasing teachers subjective well-being. The implications of the results of this study become a reference for school institutions to pay more attention to the subjective well-being of teachers by designing strategies to improve teacher-parent relationship.